Necessary functionalities for traditional and electronic active reading - Ibrahim, Nurulhuda; Othman, Azliza (2010)
Reading is an active skill-based process of constructing meaning and/or gaining knowledge from oral,visual, and written text. I1 is a means of language acquisition, of communicalion, and of sharing information and ideas (wikipedia.org, 2009). People may read a book for their own reason such as reading for improve knowledge, or for entertainment. Readingfiequently involves nor just looking at words on apage, but also underlining, highlighting and commenting, either on the text or in a separate notebook. This combination of reading wirh critical thinking and learning is called active reading. Readers used to interact with printed document for grearer understanding. However. reading on screen limits the interacrion. Thus, certain aspects of book metaphor should be retained to allow readers to experience the same activities while reading on screen. However there are similarities and dissimilariries between necessary functionaliries for traditional and electronic reading. This paper rries to determine necessary functionalities for both reading mefhods. The research framework involves two reading walkthroughs, and user surveys. Afrer each reading walkthrough, respondents were required to answer a quiz and their assessment is recorded. Thejinding of rhis study is preferences offunctionalities for rraditional andelecrronic readingpracrices.